The Role Of Public Spending In SustainableAnd Resilient Development In Costa Rica - Hartley-Ballestero, Marjorie (2026)
This research reviews some mechanisms with which fiscal policy can contribute through public spending, with the achievement of the Sustainable Development Goals and the 2030 Agenda. Of particular interest are the objectives aimed at mitigating and adapting Costa Ricansociety to the onslaught of climate change, in a context of fiscal deficit and occurrence of climatic events that challenge economic policy. It is based on recommendations made by various internationalorganizations to make fiscal policy compatible with environmental policy and sustainable development. These elements are not found when we want to evaluate the role of fiscal policy in sustainable and resilient development; on the contrary, cohesion, coherence, governance and leadership are needed in public spending policy in Costa Rica, in order to reorient to the various sectors towards the achievement of social, environmental and economic objectives. The current characteristics of climate accounting and public spending in general do not facilitate and rather limit the possibilities of an evaluation of the role of fiscal policy in achieving the SDGs.